Towards a nuanced explanation of technology adoption determinants - Salim, Siti Aisyah; Mohamad Rasli, Roznim; Abdul Aziz, Nor Azah; Mohd Razali, Fadhlina; Mohammed, Siti Asma (American Scientific Publishers, 2018)
This research proposes that the adoption of business technology should be viewed through a new lens. This is parallel with the foundational knowledge of practice that suggests the decision to adopt a new business technology should be treated as a multi-level where the level of importance of each adoption factor will perform differently depending on the position where the adoption factor will be measured. Given the above scenario, this research aims to explore business technology adoption factors (i.e., determinants) in a structured manner where each of the determinant is measured at different stages. Furthermore, this research also aims to view the synergistic relationship between different adoption determinants in order to provide the maximum level of intention towards adopting new technology. The second aim of this research could be achieved through non-linear techniques. In identifying the intention determinants, the Theory of Planned Behavior will be adopted. Meanwhile, Ettlie’s multi-stage model will be used to observe the progression of superior and inferior adoption determinants towards the highest level of intention of adoption. In illustrating the above scenario, the adoption of corporate-wide systems by small and medium-sized enterprises (SMEs) will be implemented.